2022
DOI: 10.1212/wnl.0000000000200356
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Neurologic Recovery 12 Months After Hospitalization for COVID-19

Abstract: Background/Objectives:Little is known about trajectories of recovery 12-months after hospitalization for severe COVID.Methods:We conducted a prospective, longitudinal cohort study of patients with and without neurological complications during index hospitalization for COVID-19 from March 10, 2020-May 20, 2020. Phone follow-up batteries were performed at 6- and 12-months post-COVID symptom onset. The primary 12-month outcome was the modified Rankin Scale (mRS) comparing patients with or without neurological com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 40 publications
4
45
0
1
Order By: Relevance
“…This also means that most impaired patients at the 2-month visit performed in the impaired range across the study timeline representing persistent CI. This contrasts against studies which have focused on severe cases of acute COVID-19 where pre-morbid neurological conditions predict cognitive deterioration 3 . Our finding of cognitive decline/failure to improve is in accordance with emerging cognitive 3,48 and brain imaging 49 studies assessing post-acute mild-moderate COVID-19 patients at 12-months post diagnosis.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This also means that most impaired patients at the 2-month visit performed in the impaired range across the study timeline representing persistent CI. This contrasts against studies which have focused on severe cases of acute COVID-19 where pre-morbid neurological conditions predict cognitive deterioration 3 . Our finding of cognitive decline/failure to improve is in accordance with emerging cognitive 3,48 and brain imaging 49 studies assessing post-acute mild-moderate COVID-19 patients at 12-months post diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…This contrasts against studies which have focused on severe cases of acute COVID-19 where pre-morbid neurological conditions predict cognitive deterioration 3 . Our finding of cognitive decline/failure to improve is in accordance with emerging cognitive 3,48 and brain imaging 49 studies assessing post-acute mild-moderate COVID-19 patients at 12-months post diagnosis. Studies with longer follow-up will be critical to determine if this trend is maintained or whether patients eventually improve 50 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…They also describe phenomenon such as forgetting why they are in a room, repeating oneself, and word finding difficulties. At 12 months post hospitalization for severe COVID-19 pneumonia, 50% of patients without prior history of dementia or cognitive abnormality had cognitive impairment [152]. Another study showed that 8% of COVID-19 survivors had persistent cognitive dysfunction [143].…”
Section: Epidemiology and Presentationmentioning
confidence: 99%